(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Lectins are proteins that bind to specific carbohydrates. They are found in most plants, aswell as in humans, microorganisms, animals, and fish. Therefore, they are found in many of the foods we eat. The most concentrated forms appear to be in edible seeds such as thosefound in cereal grains and legumes. The edible seeds of the legume plant (Leguminosae) may be referred to as pulses, legumes, dried beans, or beans.Lectin levels in plants and food crops can vary significantly depending on environmental conditions such as drought and salinity. Lectin compounds may have evolved in plants as asurvival mechanism, reducing the chance the they will beconsumed in large amounts.